Uplift and subsidence reveal a nonpersistent megathrust rupture boundary (Sitkinak Island, Alaska) - Briggs, Richard W.; Engelhart, Simon E.; Nelson, Alan R.; Dura, Tina; Kemp, Andrew C.; Haeussler, Peter J.; Corbett, D. Reide; Angster, Stephen J.; Bradley, Lee-Ann (Geophysical Research Letters, 2014)
We report stratigraphic evidence of land-level change and tsunami inundation along the Alaska-Aleutian megathrust during prehistoric and historical earthquakes west of Kodiak Island. On Sitkinak Island, cores and tidal outcrops fringing a lagoon reveal five sharp lithologic contacts that record coseismic land-level change. Radiocarbon dates, 137Cs profiles, computerized tomography scans, and microfossil assemblages are consistent with rapid uplift circa 290–0, 520–300, and 1050–790 cal yr B.P. and subsidence in A.D. 1964 and circa 640–510 cal yr B.P. Radiocarbon, 137Cs, and 210Pb ages bracketing a sand bed traced 1.5 km inland and evidence for sudden uplift are consistent with Russian accounts of an earthquake and tsunami in A.D. 1788. The mixed uplift and subsidence record suggests that Sitkinak Island sits above a nonpersistent boundary near the southwestern limit of the A.D. 1964 Mw 9.2 megathrust rupture.